Tafamidis treatment in patients with transthyretin amyloid cardiomyopathy: a systematic review and meta-analysisResearch in context - Jie Wang; Hongyu Chen; Zihuan Tang; Jinquan Zhang; Yuanwei Xu; Ke Wan; Kifah Hussain; Georgios V. Gkoutos; Yuchi Han; Yucheng Chen (EClinicalMedicine, 2023)
Summary: Background: Previous studies have reported that tafamidis treatment was associated with better outcomes in patients with transthyretin amyloid cardiomyopathy (ATTR-CM) compared with those without tafamidis treatment. Therefore, we aimed to systematically assess the association of tafamidis treatment with outcomes in patients with ATTR-CM. Methods: The protocol for this systematic review and meta-analysis was registered in the PROSPERO (CRD42022381985). Pubmed, Ovid Embase, Scopus, Cochrane Library, and Web of Science were interrogated to identify studies that evaluated the impact of tafamidis on prognosis in ATTR-CM, from January 1, 2000 to June 1, 2023. A random-effects model was used to determine the pooled risk ratio (RR) for the adverse endpoints. In addition, the main outcomes included all-cause death or heart transplantation, the composite endpoints included all-cause death, heart transplantation, cardiac-assist device implantation, heart failure exacerbations, and hospitalization. Findings: Fifteen studies comprising 2765 patients (mean age 75.9 ± 9.3 years; 83.7% male) with a mean follow-up duration of 18.7 ± 17.1 months were included in the meta-analysis. There was a decrease in left ventricular ejection fraction (LVEF) (standard mean differences (SMD: −0.17; 95% confidence interval (CI), −0.31 to −0.03; P = 0.02) but were no significant differences in intraventricular septum (IVS) thickness or global longitudinal strain (GLS) after tafamidis treatment. However, subgroup analysis showed no significant deterioration in LVEF in the patients with wild-type ATTR after tafamidis treatment (SMD: −0.11; 95% CI, −0.34 to 0.12, P = 0.34). In addition, the group with tafamidis treatment had a decreased risk for all-cause death or heart transplantation compared to patients without treatment (the pooled RR, 0.44; 95% CI, 0.31–0.65; P < 0.01). Subgroup analysis showed that there was no significant difference of tafamidis on the outcomes in patients with wild-type or hereditary ATTR (RR, 0.44; 95% CI, 0.27–0.73 versus 0.21, 95% CI, 0.11–0.40, P = 0.08). Furthermore, tafamidis treatment was associated with a lower risk of the composite endpoint (RR, 0.57; 95% CI, 0.42–0.77; P < 0.01). Interpretation: Our findings suggested that there was no significant deterioration in LVEF in the patients with wild-type ATTR after tafamidis treatment. In addition, tafamidis treatment was associated with a low risk of all-cause death and adverse cardiovascular events. Funding: This work was supported by grants from the Natural Science Foundation of Sichuan Province [Grant Number: 23NSFSC4589] and the National Natural Science Foundation of China [Grant Number: 82202248].